Participatory Experiences of Women in Economic Development Cooperatives in Bhambayi, KwaZulu-Natal, South Africa. (March 2017) - Raniga, Tanusha
Purpose: Nation states in both the Global North and South have debated the human rights and liberatory function as opposed to the dependency and economically viable function of social protection policy. This article is an attempt to advance empirical knowledge in the field of social protection policy and poverty alleviation. Method: Using participatory action methodology, I present evidence from 11 women who were involved in an arts and craft economic development cooperative in a community named Bhambayi in KwaZulu-Natal, South Africa. Results: Underscored by the asset-based community development and sustainable livelihood frameworks, this article presents three themes: positive contributions to human capacity development, supportive intersectoral collaboration, and striving for economic self-reliance. Conclusions: This article proposes fresh strategies for women who find themselves outside the circle of secure economic livelihoods to move beyond short-term and survival strategies and work toward economic inclusion.